Intravenous Thrombolysis Administration 3–4.5 h After Acute Ischemic Stroke: A Retrospective, Multicenter Study - Chen, Yu-Wei; Sung, Sheng-Feng; Chen, Chih-Hung; Tang, Sung-Chun; Tsai, Li-Kai; Lin, Huey-Juan; Huang, Hung-Yu; Po, Helen L.; Sun, Yu; Chen, Po-Lin; Chan, Lung; Wei, Cheng-Yu; et al. (Frontiers in Neurology, 2019)
Background and Objectives: Intravenous recombinant tissue plasminogen activator (rt-PA) has been approved for acute ischemic stroke (AIS) within 3 hours after onset, and was then extended to 4.5 hours. However, the Food and Drug Administration did not approve the indication in the expanded time window. This retrospective, matched cohort study aims to investigate the effectiveness and safety of rt-PA in AIS at 3-4.5 hours after onset. Materials and methods: The treatment group included AIS patients receiving rt-PA at 3-4.5 hours after onset, otherwise complied with the regulation, in the stroke registries in 16 hospitals between 2008 and 2017. The control group included age- and sex-matched patients not receiving intravenous thrombolysis from the same registries, excluding those with contraindications. The primary outcome was modified Rankin Scale (mRS) 0-1 at day 90. The safety outcomes were any intracerebral hemorrhage (ICH), early neurological deterioration and 3-month mortality. Results: Each group had 374 patients. There were 34.0% of patients with 3-month mRS 0-1 in the treatment group vs. 22.7% in the control group with an odds ratio of 1.75 (95% confidence intervals, 1.27 to 2.42, P=0.001). There was no difference in symptomatic ICH, early neurological deterioration and 3-month mortality rates between two groups. The 3-month mRS and symptomatic ICH did not differ significantly in patients receiving standard dose or low dose of rt-PA. Conclusions: Our results support the prescription of rt-PA in AIS patients 3-4.5 hours after onset as an effective and tolerable treatment in their functional recovery.